Evaluation of commercial roasting parameters for pork belly - Garcia, Benedict Alano
ABSTRACT This study aimed to examine the commercial processes employed in the Philippines for the roasting of pork belly including the roasting procedures, thermal profile and, thermal properties of the pork. The roasting parameters were evaluated to assess its influence on the physical characteristics of the roasted pork belly. The design of charcoal heated ovens used by three popular commercial pork belly roasting establishments in Las Pinas and Quezon City, Philippines essentially consisted of steel framed glass (about 200x80x80cm) with two levels of rotisseries. The basal marinade used for roasted pork bellies generally included: soy sauce, salt, pepper and garlic. The commercial procedure for roasting pork belly involved low temperature roasting at 60-80°C initially done at the 2nd level rotisserie for 15 min and then at the 1st level rotisserie for higher temperature roasting at about 150°C for another 30 min or until the rind is evenly puffed and the meat turned to golden brown. The doneness of roasting is based on visual properties of the meat and experience of the cook. Cooking losses of 37% were recorded after the roasting process and reductions in the dimensions of the pork belly were observed due to meat protein denaturation and melting of fats. The distinct areas of the pork belly identified as the rib, true belly and hind limb areas have lean to fat ratios of 1:1, 1:2 and 2:1, respectively. The ratios were based on the average relative thickness (cm) of the fat and lean section of the pork belly. The recorded general trend for fastest roasting rate and highest internal temperature attained in the various areas of the pork belly were as follows: true belly> rib> hind limb. The fastest heating rate of 2.00°C/min in the true belly area with highest internal temperature of 99°C were attributed to its relatively thicker fat and thinner lean meat profile. The larger heat capacity (0.46 cal/g°C) and density (0.90 g/ml) of the hind limb area attributed to its high lean meat composition and slower heating rate. Given the established thermal characteristics of the pork belly using commercial conditions for roasting, processors should base their roasting protocols relative to the hind limb area of the pork belly since heating rate was found to be slowest in this section. This step would ensure that pork belly is adequately cooked. The current commercial cooking practices for roasting of pork belly can also be modified since the existing procedure could affect an internal meat temperature of about 90°C which is beyond the recommended 77°C by the USDA (2003). Lowering the roasting temperature or time may increase the yield of the roasted pr